Promoting Earth Buildings for Residential Construction in New Zealand - Don Amila Sajeevan Samarasinghe; Stephanie Falk (Buildings, 2022)
The construction of earth buildings, both throughout history and in the current day, is well-established worldwide. Despite New Zealand’s pre- and post-colonial history of earth construction, earth buildings as residential homes have not been well-received or popularised throughout present-day New Zealand. This research aims to identify the reasons for this lack of awareness and to determine methods that promote earth buildings in New Zealand. This research is based on data collected from semi-structured interviews conducted with subject matter experts and via an online questionnaire completed by members of the Earth Building Association New Zealand (EBANZ). The data collected revealed the experiences and perceptions of all participants regarding the advantages, challenges and promotion of earth buildings specific to New Zealand. Following analysis of these responses, key reoccurring themes were identified and compared. Regarding New Zealand’s lack of awareness of earth buildings, interview and questionnaire participants responded that this shortcoming was due to earth construction being a very niche market and lacking commercial marketing. Education was the most frequently reoccurring theme raised by all participants as the top promotional tool for raising awareness of earth buildings. The results of this research can be applied to future work regarding obstacles that limit the growth of New Zealand’s earth building industry, as well as research on the role of New Zealand’s education system in exposing the next generation of builders, designers, and consumers to earth construction.